GAMBARAN PENGELOLAAN OBAT DI INSTALASI FARMASI RSUD PROF. Dr. H. ALOEI SABOE KOTA GORONTALO - Salsabila Pratiwi Abdullah (Yayasan Nusantara Hasana Berdikari, 2025)
Pharmaceutical service standards are benchmarks used as guidelines for pharmaceutical personnel in organizing pharmaceutical services including drug management. The purpose of this study was to description drug management in the Pharmacy Installation of Prof. Dr. H. Aloei Saboe Regional General Hospital reviewed from the standards of pharmaceutical services in hospitals. This study was conducted using qualitative and quantitative methods descriptively, observations were conducted using checklists, structured interviews with interview guidelines and document reviews. From the results of the study, it is known that the profile of drug management in the Pharmacy Installation of Prof. Dr. H. Aloei Saboe Regional General Hospital, Gorontalo City in the aspects of selection, planning needs, procurement, receipt, distribution, destruction and withdrawal, control, and administration obtained a percentage of conformity of 100% and was categorized as Very Good, while in the Storage aspect only obtained a percentage of conformity of 88.13% and was categorized as Very Good because there were still requirements that had not been met. The conclusion of this study is that drug management at the Pharmacy Installation of Prof. Dr. H. Aloei Saboe Regional General Hospital, Gorontalo City is not fully in accordance with the Regulation of the Minister of Health Number 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals and Technical Instructions for Pharmaceutical Service Standards in Hospitals in 2019.